An Analysis of Figurative Language in Maroon 5 – Nobody’s Love Song Lyrics - Farhan Muhammad; Didin Nuruddin Hidayat; Alek Alek (LPPM Universitas Bina Sarana Informatika, 2021)
Beautiful words have special meanings and involve expressing ideas in song lyrics through figurative language. This study discussed an analysis of the figurative language in the Maroon 5 song’s lyrics. This study emphasizes the use of figurative language and meaning in the lyrics of the song